Effect of drying methods on total flavonoid content of Scurrula ferruginea (Jack) Danser (Loranthaceae) leaf extracts parasitizing jengkol (Pithecellobium jiringa) - Fatridha Yansen; Eldya Mossfika; Heppy Setya Prima (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2025)
Scurrula ferruginea (Benalu) is a hemiparasitic plant with potential as a raw material for traditional medicine due to its high flavonoid content. The concentration of flavonoids is substantially determined by the specific drying technique applied. Studies investigating the use of the stir-frying method remain limited, and there is no standardized protocol has yet been established to recommend an appropriate method for preserving the total flavonoid content in S. ferruginea leaves. This study aims to compare the total flavonoid content (TFC) in ethanol extracts of Benalu leaves on the Jengkol dried using three different methods: air-drying, oven-drying, and stir-frying drying. All samples were subsequently powdered and subjected to maceration using ethanol solvent, followed by analysis of their total flavonoid content using spectrophotometry UV-Vis at maximum wavelength at 431 nm. Statistical analysis of one-way ANOVA showed that different drying methods generated significant effects on TFC level of Benalu leaves extracts with significance value = 0.001 (p-value <= 0.05). The results indicated that air-drying yielded the highest flavonoid content with 7.37 ppm, followed by stir-frying (4.93 ppm) and oven-drying (2.88 ppm). These findings highlight the critical importance of selecting an appropriate drying method to preserve flavonoid levels, thereby enhancing the pharmacological efficacy and quality of herbal products derived from S. ferruginea leaves.